At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Which ordered pair makes both inequalities true?

[tex]\[
\begin{array}{l}
y \ \textgreater \ -3x + 3 \\
y \geq 2x - 2
\end{array}
\][/tex]

A. \((1,0)\)

B. \((-1,1)\)

C. \((2,2)\)

D. [tex]\((0,3)\)[/tex]


Sagot :

To determine which ordered pair \((x, y)\) satisfies both inequalities:
[tex]\[ y > -3x + 3 \][/tex]
[tex]\[ y \geq 2x - 2 \][/tex]

we need to check each pair against both inequalities.

1. Pair (1, 0):
- First inequality: \( y > -3x + 3 \)
[tex]\[ 0 > -3(1) + 3 \rightarrow 0 > 0 \][/tex] (False)
- Second inequality: \( y \geq 2x - 2 \)
[tex]\[ 0 \geq 2(1) - 2 \rightarrow 0 \geq 0 \][/tex] (True)

This pair does not satisfy the first inequality, so (1, 0) is not a solution.

2. Pair (-1, 1):
- First inequality: \( y > -3x + 3 \)
[tex]\[ 1 > -3(-1) + 3 \rightarrow 1 > 6 \][/tex] (False)
- Second inequality: \( y \geq 2x - 2 \)
[tex]\[ 1 \geq 2(-1) - 2 \rightarrow 1 \geq -4 \][/tex] (True)

This pair does not satisfy the first inequality, so (-1, 1) is not a solution.

3. Pair (2, 2):
- First inequality: \( y > -3x + 3 \)
[tex]\[ 2 > -3(2) + 3 \rightarrow 2 > -3 \][/tex] (True)
- Second inequality: \( y \geq 2x - 2 \)
[tex]\[ 2 \geq 2(2) - 2 \rightarrow 2 \geq 2 \][/tex] (True)

This pair satisfies both inequalities, so (2, 2) is a solution.

4. Pair (0, 3):
- First inequality: \( y > -3x + 3 \)
[tex]\[ 3 > -3(0) + 3 \rightarrow 3 > 3 \][/tex] (False)
- Second inequality: \( y \geq 2x - 2 \)
[tex]\[ 3 \geq 2(0) - 2 \rightarrow 3 \geq -2 \][/tex] (True)

This pair does not satisfy the first inequality, so (0, 3) is not a solution.

Thus, the ordered pair [tex]\((2, 2)\)[/tex] makes both inequalities true.